Heoretical and practical foundations of organizing and developing agro-cluster activities - Berdiyev Abdumalik Hakimovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the theoretical and practical foundations of organizing and developing agro-clusters. The economic essence of agro-clusters and their role in strengthening cooperation and integration processes in agriculture are revealed. The opportunities for creating a value-added chain through the integration of agribusiness entities, processing enterprises, logistics, and service infrastructure are also highlighted. From a practical perspective, the priority directions for the development of agro-clusters include the introduction of innovative technologies, the expansion of digital management systems, the enhancement of export potential, and the improvement of the training system for specialists. Based on domestic and international experience, scientific conclusions and practical recommendations for the effective development of agro-industrial clusters have been developed.